2000
DOI: 10.1021/bi9914208
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutamate-268 in the Catalytic Mechanism of Nonphosphorylating Glyceraldehyde-3-phosphate Dehydrogenase from Streptococcus mutans

Abstract: Nonphosphorylating nicotinamide adenine dinucleotide (phosphate)- [NAD(P)-] dependent aldehyde dehydrogenases share a number of conserved amino acid residues, several of which are directly implicated in catalysis. In the present study, the role of Glu-268 from nonphosphorylating glyceraldehyde-3-phosphate dehydrogenase (GAPN) from Streptococcus mutans was investigated. Its substitution by Ala resulted in a k(cat) decrease by 3 orders of magnitude. Pre-steady-state analysis showed that, for both the wild-type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
75
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 16 publications
9
75
0
Order By: Relevance
“…2). According to the reaction mechanism suggested by Marchal et al (53) (Glu 250 ) activates the subsequent deacylation step by directed hydrolysis of the thioester bond. However, in the conformation observed in the crystal structure presented here, the distance between the side chain atoms of Glu 263 and Cys 297 is ϳ6 Å (Fig.…”
Section: Fig 2 Structure-based Sequence Alignment Of Tt-gapn Sm-gamentioning
confidence: 99%
See 1 more Smart Citation
“…2). According to the reaction mechanism suggested by Marchal et al (53) (Glu 250 ) activates the subsequent deacylation step by directed hydrolysis of the thioester bond. However, in the conformation observed in the crystal structure presented here, the distance between the side chain atoms of Glu 263 and Cys 297 is ϳ6 Å (Fig.…”
Section: Fig 2 Structure-based Sequence Alignment Of Tt-gapn Sm-gamentioning
confidence: 99%
“…In class 3 ALDH, however, this residue seems to be involved only in cosubstrate binding. In the case of Sm-GAPN, this residue has been suggested to play an essential role in deacylation by activating a water that hydrolyzes the intermediate (53).…”
mentioning
confidence: 99%
“…It has also been suggested that, in tetrameric class 1 and 2 ALDHs, the proton abstracted by Glu-268 is shuttled to bulk water (10,25). In addition, Glu-268 is also the most likely residue activating a water molecule in the deacylation step of the reaction (5,7,10,23,26).…”
mentioning
confidence: 99%
“…This gave us the opportunity to determine the pK app of CoA in the deacylation step, which shifts from ϳ9.6 to 6.8. When compared with a chemical model, the catalytic efficiency of the transthioesterification for the wild-type MSDH was increased at least 10 4 -fold. Therefore, CoA binding to MSDH optimizes its positioning relative to the thioacyl enzyme intermediate and favors a significant decrease of the pK app of its thiol group.…”
mentioning
confidence: 99%